Update on 3-iodothyronamine and its neurological and metabolic actions - Zucchi, Riccardo; Accorroni, Alice; Chiellini, Grazia (Frontiers in Physiology, 2014)
3-iodothyronamine (T1AM) is an endogenous amine, that has been detected many rodent tissues, and in human blood. It has been hypothesized to derive from thyroid hormone metabolism, but this hypothesis still requires validation. T1AM is not a ligand for nuclear thyroid hormone receptors, but stimulates with nanomolar affinity trace amine-associated receptor 1 (TAAR1), a G protein-coupled membrane receptor. With a lower affinity it interacts with alpha2A adrenergic receptors. Additional targets are represented by apolipoprotein B100, mitochondrial ATP synthase, and membrane monoamine transporters, but the functional relevance of these interactions is still uncertain. Among the effects reported after administration of exogenous T1AM to experimental animals, metabolic and neurological responses deserve special attention, because they were obtained at low dosages, which increased endogenous tissue concentration by about one order of magnitude. Systemic T1AM administration favored fatty acid over glucose catabolism, increased ketogenesis and increased blood glucose. Similar responses were elicited by intracerebral infusion, which inhibited insulin secretion and stimulated glucagon secretion. However, T1AM administration increased ketogenesis and gluconeogenesis also in hepatic cell lines and in perfused liver preparations, providing evidence for a peripheral action, as well. In the central nervous system, T1AM behaved as a neuromodulator, affecting adrenergic and/or histaminergic neurons. Intracerebral T1AM administration favoured learning and memory, modulated sleep and feeding, and decreased the pain threshold. In conclusion T1AM should be considered as a component of thyroid hormone signalling and might play a significant physiological and/or pathophysiological role. T1AM analogues have already been synthetized and their therapeutical potential is currently under investigation.